2012
DOI: 10.1002/gcc.21994
|View full text |Cite
|
Sign up to set email alerts
|

Three‐way translocation (X;20;16)(p11;q13;q23) in essential thrombocythemia implicates NFATC2 in dysregulation of CSF2 expression and megakaryocyte proliferation

Abstract: Essential thrombocythemia (ET) is a myeloproliferative neoplasm essentially characterized by excessive production of platelets. Molecular pathogenesis of ET is linked in approximately half of the patients to intracellular cytokine signaling dysregulation as a result of thrombopoietin receptor or Janus kinase 2 (JAK2) mutations. However, genetic defects underlying cytokine transcription have not been associated with ET. Using molecular cytogenetics and whole-genome array analyses, we uncovered a submicroscopic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…FKBP5, another calcineurin inhibitor, was found to be upregulated in myelofibrosis [177]. Furthermore, in one patient with essential thrombocythaemia, a three-way translocation which created a breakpoint in NFATC2 was identified possibly contributing to the overproliferation of MKs [178].…”
Section: Nfatmentioning
confidence: 98%
“…FKBP5, another calcineurin inhibitor, was found to be upregulated in myelofibrosis [177]. Furthermore, in one patient with essential thrombocythaemia, a three-way translocation which created a breakpoint in NFATC2 was identified possibly contributing to the overproliferation of MKs [178].…”
Section: Nfatmentioning
confidence: 98%
“…NFATC2 also controls the cell-cycle progression by repressing expression of the G0–G1 checkpoint kinase CDK4 and cyclins A2, BA, E and F [75][77], and induces apoptosis in NIH3T3 fibroblasts in cooperation with the Ras/Raf/MEK/ERK pathway [63]. Recently, it was reported that haploinsufficency of NFATC2 contributes to the pathogenesis of essential thrombocythemia with del(20q) [78]. In this context, particularly interesting is the study of Caloca et al .…”
Section: Discussionmentioning
confidence: 99%
“…Forty to fifty percent of the patients carry the Janus kinase 2 (JAK2) V617F or a functionally similar mutation, but these mutations are not specific for ET, because they are found in polycythemia vera and primary myelofibrosis as well (Cho et al 2009;Deepak et al 2011;Kiladjian 2012;Martinez-Avilez et al 2012;Pich et al 2012). One percent of ET patients show a gain of function mutation of MPL, MPL W515K/ L. In patients with JAK2 V617F-positive ET with del(20q), haploinsufficiency of the nuclear factor of activated T-cells, cytoplasmic, calcineurindependent 2/NFATC2 seems to cooperate with activation of the JAK-STAT signaling pathway (Vieira et al 2012). Mutations of TET2 (tet oncogene family member 2) were detected in both JAK-positive and JAK-negative ET, but only in a minority of cases and more often in older patients (Tefferi et al 2009;Martinez-Aviles et al 2012).…”
Section: Cytogenetic and Molecular Featuresmentioning
confidence: 99%